Topical Formulation of Noscapine, a Benzylisoquinoline Alkaloid, Ameliorates Imiquimod-Induced Psoriasis-Like Skin Lesions. (22nd April 2022) - Nourbakhsh, Fahimeh; Mousavi, Seyed Hadi; Rahmanian-Devin, Pouria; Baradaran Rahimi, Vafa; Rakhshandeh, Hassan; Askari, Vahid Reza
Abstract : Psoriasis is considered an autoimmune inflammatory disease. The disease is spread and diagnosed by the infiltration of inflammatory mediators and cells into the epidermis. Recent theoretical developments have focused on the effectiveness of noscapine (NOS) as a potential alkaloid for being used as a valuable treatment for different diseases. In the present study, psoriasis-like dermatitis was induced on the right ear pinna surface of male Balb/c mice by topical application of imiquimod (IMQ) for ten consecutive days, which was treated with noscapine (0.3, 1, 3, and 10% w/v) or clobetasol (0.05% w/v) as a positive control. The levels of ear length, thickness, severity of skin inflammation, psoriatic itch, psoriasis area severity index (PASI) score, and body weight were measured daily. On the 10 th day of study, each ear was investigated for inflammation, fibrosis, proliferation, and apoptosis using histopathological (H&E and Masson's trichrome staining) and immunohistochemistry (Ki67 and p53 staining) assays. Furthermore, the levels of inflammatory biomarkers were characterized by an enzyme-linked immunosorbent assay (ELISA). The results confirmed IMQ-induced psoriasis for five consecutive days. In contrast, noscapine significantly reduced the ear length, thickness, severity of skin inflammation, psoriatic itch and body weight, tumor necrosis factor- α (TNF- α ), transforming growth factor- β (TGF- β ), interferon-gamma (IFN- γ ), interleukin 6 (IL-6), IL-17, and IL-23p19 in a concentration-dependent manner ( P < 0.001–0.05 for all cases). Overall, topical noscapine significantly ameliorated both the macroscopical and microscopical features of psoriasis. However, further clinical investigations are required to translate the effects to clinics.